The Comparison of Biocompatibility Properties between Ti Alloys and Fluorinated Diamond-Like Carbon Films - Chavin Jongwannasiri; Nutthanun Moolsradoo; Anak Khantachawana; Pongpan Kaewtatip; Shuichi Watanabe (Advances in Materials Science and Engineering)
Titanium and titanium alloys have found several applications in the biomedical field due to their unique biocompatibility. However, there are problems associated with these materials in applications in which there is direct contact with blood, for instance, thrombogenesis and protein adsorption. Surface modification is one of the effective methods used to improve the performance of Ti and Ti alloys in these circumstances. In this study, fluorinated diamond-like carbon (F-DLC) films are chosen to take into account the biocompatible properties compared with Ti alloys. F-DLC films were prepared on NiTi substrates by a plasma-based ion implantation (PBII) technique using acetylene (C2H2) and tetrafluoromethane (CF4) as plasma sources. The structure of the films was characterized by Raman spectroscopy. The contact angle and surface energy were also measured. Protein adsorption was performed by treating the films with bovine serum albumin and fibrinogen. The electrochemical corrosion behavior was investigated in Hanks’ solution by means of a potentiodynamic polarization technique. Cytotoxicity tests were performed using MTT assay and dyed fluorescence. The results indicate that F-DLC films present their hydrophobic surfaces due to a high contact angle and low surface energy. These films can support the higher albumin-to-fibrinogen ratio as compared to Ti alloys. They tend to suppress the platelet adhesion. Furthermore, F-DLC films exhibit better corrosion resistance and less cytotoxicity on their surfaces. It can be concluded that F-DLC films can improve the biocompatibility properties of Ti alloys.